Comparative analysis of dynamic load models generated by runners on footbridges - Marek Pańtak (Archives of Civil Engineering, 2023)
Footbridges, like all building structures, must be designed in a way that ensures their safe and comfortable use. Steel footbridges characterised by low vibration damping often turn out to be a structure susceptible to the dynamic influence of users during various forms of their activity. For these structures, the impact of running users may be a key type of dynamic load for the verification of the serviceability limit state due to vibrations. In the literature, there are several proposals for models of dynamic load generated by runners (models of ground reaction forces – GRF). The paper presents the characteristics, analyses and comparisons of selected GRF load models. The analyses were performed using the GRF recorded during the laboratory tests of runners (tests planned and carried out by the author) and the GRF determined using various load models. In order to illustrate the accuracy of the estimation of the dynamic response of the structure, depending on the GRF model used, dynamic field tests and dynamic numerical analyses of the selected steel footbridge were carried out. The obtained results were analysed and compared.